Lokaniti: Method of Adaption and New Vocabulary - Kumar, Ujjwal (Buddhist Studies Review, 2017)
In this paper I have made an attempt to discuss the adaptation method and new vocabulary employed and introduced by the Lokaniti (Ln). This text was composed in Burma most probably by Catrungabala around the fourteenth century CE. In premodern Burma Ln was used in monasteries to inculcate guidance on worldly affairs and everyday morality to the Burmese householders in general and to the Buddhist monks in particular.